Opposite physiological effects upon jasmonic acid and brassinosteroid treatment on laticifer proliferation and co-occurrence of differential expression of genes involved in vascular development in rubber tree - Poochita Arreewichit (2020)
© 2019, Prof. H.S. Srivastava Foundation for Science and Society. During growth of woody plant-trunk, the secondary meristem functions in giving rise the xylem and phloem. Rubber tree (Hevea brasiliensis Muell. Arg.), in addition, contains laticifers (latex producing vessels) in the vicinity of phloem. Insights into regulatory mechanisms of gene networks underlying laticifer proliferation in rubber tree has remained very limited. The candidate vascular development-related genes were selected to investigate for expression profile in phloem and xylem tissues of high latex yield- and high wood yield-clones of rubber tree. The differential gene expression between the mature branch-xylem and -phloem tissues was clearly observed. The cis-regulatory motif analysis revealed the existent of putative jasmonic acid (JA)- and brassinosteroid (BR)-responsive regulatory motifs in promoter regions of these genes, and consequently the effect of exogenous application of JA, BR or their respective signaling inhibitors, on the formation of laticifers in rubber tree was demonstrated. Interestingly, the laticifer numbers were significantly increased in JA-treatment, correlated with up-regulation of phloem development-related genes in both rubber tree clones. On the contrary, the laticifers were decreased in BR-treatment accompanying by up-regulation of xylem development-related genes, especially in high wood yield-rubber tree clone. BR-inhibitor treatment also enhanced laticifer numbers, while JA-inhibitor suppressed laticifer differentiation. Taken together, this study unveils the molecular interplay between JA/BR on vascular development in rubber tree and how this impacts the appearance of laticifers in this plant. This process is vital for a better understanding on laticifer differentiation and its impact in the manipulation of wood and latex yield in rubber tree improvement program.